Zoombombing – the end-to-end fallacy. Issue 8 (August 2020) - Secara, Ion-Alexandru
Abstract : Zoombombing, a trend in recent months, has quickly moved from online classroom pranks to organised disruption efforts, which the FBI has threatened to punish with jail time. "The FBI has received multiple reports of conferences being disrupted by pornographic and/or hate images and threatening language." the agency stated in a recent press release. 1 Zoombombing has quickly moved from online prank to organised disruption effort, which the FBI has threatened to punish with jail time. As the use of Zoom has increased dramatically due to the Covid-19 pandemic, multiple security issues have emerged concerning the platform. The company is taking steps to bring the platform up to date with industry standards. But the issue clearly shows that certain companies focus more on the functionality they provide to their users than they do on the appropriate security, says Ion-Alexandru Secara.